Nutritional support during pregnancy - K. B. Mozes; S. I. Elgina; V. G. Mozes; E. V. Rudaeva; N. M. Shibelgut; O. S. Chaplygina; T. E. Pomytkina (IRBIS LLC, 2024)
Aim: to summarize new data regarding the effectiveness of nutritional support during pregnancy.Materials and Methods. A search for publications was carried out in the PubMed/MEDLINE, Scopus, Web of Science, RSCI databases by retrieving queries for the following keywords: nutritional support, pregnancy, micronutrients, vitamins, macronutrients, without language restrictions. 71 sources with full text access were selected for analysis.Results. Nutritional status during pregnancy markedly impacts on mother's and neonate's health. During pregnancy, requirements for macro- and micronutrients increase to maintain maternal homeostasis and support fetal growth. Increasing calorie intake in general female population demonstrates modest effects on pregnancy and fetal outcomes, whereas for pregnant women in poor income countries it results in no long-term benefits for children by assessing their anthropometric parameters and neurocognitive development. Despite the lack of conclusive evidence, in many countries sensible calorie restriction during pregnancy is recommended. Some micronutrients are vital for mother and fetus, because their deficiency is accompanied by increased risk of adverse pregnancy outcomes. For instance, folic acid deficiency is associated with the risk of developing fetal neural tube defects, iodine deficiency is coupled to the risk of emerging pediatric intellectual development disorders associated with congenital hypothyroidism, and calcium deficiency is related to a high risk of maternal hypertensive disorders. Therefore, micronutrient supplementation represents a technology with good potential in fighting for maternal and child health. Nonetheless, despite some advances in understanding nutritional support in pregnant women, many studies provide controversial data substantiating a need to conduct further investigations.Conclusion. Overall, recent year research confirms that the supplementation of micro- and macronutrients during pregnancy is an effective tool for "fetal programming" allowing to impact on maternal and fetal health. At the same time, an analysis of the literature showed a significant lack of research in the field of creating individual nutrition programs and nutritional support for pregnant women belonging to different segments of the population, living in different geographical regions, etc.